Unveiling air quality shifts during Diwali in Chennai using geospatial insights for pollution assessment - Senapathi, Venkatramanan; Murugesan, Bagyaraj; Balasubramaniam, Gurugnanam; Swaminathan, Bairavi; Karthikeyan, Sivakumar; Barzegar, Rahim; Nadiri, Ata Allah (Discover Geoscience, 2025)
Air pollution poses a significant challenge to global health, contributing to one in nine fatalities worldwide and causing approximately seven million premature deaths annually, according to the World Health Organization (WHO). In South Asia, air pollution ranks as the sixth leading cause of mortality, exacerbating issues such as poor visibility, respiratory illnesses, and elevated death rates. This study examines the impact of fireworks emissions on air quality in Chennai during the Diwali festival, focusing on particulate matter (PM 2.5 , PM 10 ) and trace gases, including nitrogen oxides (NO 2 ), ammonia (NH 3 ), sulfur dioxide (SO 2 ), carbon monoxide (CO), and ozone (O 3 ). Measurements recorded before and after Diwali festival on October 26, 2022, revealed mean 24-h PM 2.5 and PM 10 concentrations of 93 µg/m 3 and 94 µg/m 3 , respectively—exceeding WHO’s emission limits. During the festival, the peak concentrations of NO 2 , NH 3 , SO 2 , CO, and O 3 were 15.83 µg/m 3 , 5.83 µg/m 3 , 25.50 µg/m 3 , 35.67 µg/m 3 , and 13 µg/m 3 , respectively, surpassing limits established by India’s Central Pollution Control Board (CPCB). Comparisons with pre-Diwali data indicated substantial increases in pollutant levels attributed to fireworks. Geographic Information System (GIS) mapping and trace gas correlation analyses highlighted the spatial and temporal distribution of pollutants. Findings suggest that short-term exposure to these elevated pollutant levels can significantly impact vulnerable populations, particularly infants, children, and individuals with respiratory conditions. To mitigate these adverse effects, the study recommends implementing restrictions on fireworks near sensitive areas such as hospitals and schools, alongside public awareness campaigns to promote sustainable practices during festive celebrations.